Modelling the spatial distribution of Sardina pilchardus and Engraulis encrasicolus spawning habitat in the NW Mediterranean Sea. (July 2021) - Gordó-Vilaseca, Cesc; Pennino, Maria Grazia; Albo-Puigserver, Marta; Wolff, Matthias; Coll, Marta
Abstract: We investigated the main drivers of eggs and larvae distributions of European sardine and anchovy from the NW Mediterranean Sea. We used Generalized Additive Models and satellite environmental data. Mainly sea surface temperature, but also currents, surface height, and primary production were significantly correlated with both species' early stages distributions. Anchovy optimal temperature upper limit was not detected, but sardine eggs and larvae presented a small-ranged bell-shape curve relationship to SST with an upper SST threshold around 13 °C. Sardine spawning during winter appeared to be dependant not only on in-situ environmental conditions but also on summer conditions prior to the spawning event. Model predictions of the larval and spawning habitat distribution showed clear differences between developmental stages and between species, confirming a worsening of the sardine habitat with time. Considering the further increase of surface temperature predicted in the years to come, the survival of the sardine in the region could be compromised. Highlights: Surface Temperature is the main explanatory variable for European anchovy and sardine early stages distribution. European sardine eggs and larval distribution are influenced by previous year conditions. Small Distributional range and low densities of European Sardine eggs and larvae during its reproductive period.